One-day supplementation with tyrosine did not affect reproductive traits of sows - I Rettmer; Jeffrey S Stevenson; Robert D Goodband; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1991)
Primiparous and multiparous sows received a single dietary supplement of L-tyrosine in their feed on the day after weaning, and the effects on various reproductive traits were evaluated. Sows received either none (control; n = 21) or 45.5 mg L-tyrosine/lb BW (tyrosine; n = 22) on the day after weaning. In Exp. 1, days from weaning to estrus (5.1 ± 1 vs 5.3 ± .9 d) and ovulation rate (number of corpora lutea on ovaries on d 5 after estrus) (16.3 ± 4.4 vs 16.2 ± 4) were similar in control and tyrosine-supplemented sows. In Exp. 2, (control; n = 63; tyrosine; n = 53) days to estrus were extended by tyrosine supplementation (6.4 ± .5 d) compared to control sows (4.6 ± .5 d), but total numbers of piglets born (10.6 ± .4 vs 10.1 ± .4) were similar in control- and tyrosine-treated groups. Therefore, a single dietary supplementation with tyrosine on the day after weaning failed to influence interval to estrus, ovulation rate, or litter traits.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Tyrosine; Sows; Weaning; Estrus; Litter size